5-Methyltetrahydrofolate in Maternal Diets Alters DNA Methylation Potential and Increases Later Life Weight Gain and Food Intake in Wistar Rat Dams and Female Offspring (P11-022-19). (13th June 2019) - Pannia, Emanuela; Hammoud, Rola; Kubant, Ruslan; Sa, Jong; Yang, Neil; Ho, Mandy; Chatterjee, Diptendu; Pausova, Zdenka; Arning, Erland; Bottiglieri, Teodoro; Anderson, G Harvey
Abstract: Objectives: Diet during pregnancy programs the mother and offspring post-weaning (PW). Folic acid (FA, synthetic folate) mediates DNA methylation (DNAm) reactions and high intakes, simulating those consumed by American women, lead to epigenetic dysregulation of energy metabolic pathways. 5-methyltetrahydrofolate (5MTHF), the bioactive folate form, has gained popularity as a supplement due to direct cellular uptake and utilization and does not increase unmetabolized FA (UMFA). However, a comparison of folate forms on in utero programming of offspring or maternal health has not been reported. Our objectives were to compare the effects of folate dose (low vs high) and form (FA vs 5MTHF) during pregnancy on DNAm potential, and the early and later PW phenotype of Wistar rat mothers and female offspring (mothers-to-be). Methods: Pregnant Wistar rats (n = 22/group) were fed an AIN93G diet with recommended FA (1X, 2mg/kg diet), 5X-FA or equimolar 5MTHF. Dams were fed 1X-FA during lactation and then dams and female pups were fed a high fat diet for 19 weeks. Weight gain (WG), food intake (FI), energy expenditure (EE), insulin resistance (IR), plasma 5MTHF, UMFA, homocysteine (tHcy), and hepatic S-adenosylmethionine (SAM), S-adenosylhomocysteine (SAH) and DNA methyltransferases (DNMT) activity at birth and PW were measured. Results: Dams fed 5MTHF diets had lower DNMT activity at birth and female pups had higher SAM: SAH ratios ( P < 0.05) indicative of altered DNAm potential compared to FA diets. Plasma 5MTHF at birth was dose dependent with 5X diets leading to higher levels than 1X diets ( P < 0.001) in dams and pups. In contrast, UMFA was only higher in 5X-FA dams. 5MTHF dams had higher tHcy at birth and were more IR at 1 week PW than FA fed dams ( P < 0.05). In both dams and offspring, high 5MTHF also led to higher WG (> 15%, P < 0.001) and FI (> 5%, P < 0.001) compared to high FA diets up to 19 weeks. EE ( P < 0.05) was higher suggesting a compensatory response to WG. 5X-MTHF dams, but not offspring, also had greater hepatic lipids ( P < 0.05) than other groups. Conclusions: Folate dose and form during pregnancy affects DNAm potential at birth and early and later phenotype of dams and female offspring. High 5MTHF increases WG, FI and hepatic lipids PW suggesting it may not be the preferred form for prenatal supplements or additions to the food supply. Funding Sources: Supported by CIHR-INMD; EP supported by NSERC-CGS D.